Coronary Angiography-Derived Index of Microvascular Resistance - Ai, Hu; Feng, Yundi; Gong, Yanjun; Zheng, Bo; Jin, Qinhua; Zhang, Hui-Ping; Sun, Fucheng; Li, Jianping; Chen, Yundai; Huo, Yunlong; Huo, Yong (Frontiers in Physiology, 2020)
A coronary angiography-derived index of microvascular resistance (caIMR) is proposed for physiological assessment of micorvasular diseases in coronary circulation. The aim of the study is to assess diagnostic performance of caIMR, using wire-derived index of microvascular resistance (IMR) as the reference standard. IMR was demonstrated in 56 patients (57 vessels) with stable/unstable angina pectoris and no obstructive coronary arteries in three centers using the Certus pressure wire. Based on the aortic pressure wave and coronary angiograms from two projections, the caIMR was computed and assessed in blinded fashion against the IMR at an independent core laboratory. Diagnostic accuracy, sensitivity, specificity, positive predictive value and negative predictive value of the caIMR with a cutoff value of 25 were 84.2% (95% CI: 72.1% to 92.5%), 86.1% (95% CI: 70.5% to 95.3%), 81.0% (95% CI: 58.1% to 94.6%), 88.6% (95% CI: 76.1% to 95.0%), and 77.3% (95% CI: 59.5% to 88.7%) against the IMR with a cutoff value of 25. The receiver-operating curve had area under the curve of 0.919. There was good correlation between caIMR and wire-derived IMR. caIMR could eliminate the need of a pressure wire, reduce technical error, and potentially increase adoption of physiological assessment of microvascular diseases in patients with ischemic heart disease.